Innovative Study of Resistor Shunt‐Based Bridged‐T Topology With Bandpass Negative Group Delay Behavior. Issue 7 (20th July 2021) - Xu, Zhifei; Nebhen, Jamel; Chan, George; Rahajandraibe, Wenceslas; Ravelo, Blaise
Abstract: In this paper, new bridged‐T network operating with bandpass (BP) negative group delay (NGD) function is introduced. The circuit design is innovatively based on an inductorless passive RC‐network. The innovative bridged‐T topology is implemented with a R‐shunt configuration. The analytical transfer function of voltages and equivalent impedance‐matrix are carefully calculated. The BP NGD analysis and design of the bridged‐T topology is developed. The BP NGD properties and specifications are analytically investigated. A proof of concept of R‐shunt bridged‐T prototype with a surface‐mounted device printed circuit board is designed, fabricated, and measured to verify the BP NGD behavior from theoretical equations and simulations. As expected, the theoretical, simulation, and measurements results are in very good agreement. From measurement results, the fabricated BP NGD C‐shunt bridged‐T reaches a delay of about −45 ns and a center frequency of about 0.5 MHz over a −3 dB attenuation. Key Points: Bandpass negative group delay Circuit theory